Dinamika Kebijakan Pemutusan Hubungan Kerja Honorer (PPDK) Oleh Bupati Morotai - Fandi Hi. Latief; Sri Ka’bah (Peneliti.net, 2022)
Keywords: Policy, Termination of Employment (PPDK) This study uses a type of qualitative research. The approach used in this study is descriptive which aims to present a problem from an observed situation. The implementation of the Honorary Termination Policy in Morotai Island Regency has drawn controversy from all aspects, starting from the honorary recruitment process due to political factors, the government's lack of sympathy in paying honorarium incentives for 8 months, to the evaluation of dismissals by regional heads. So that in its development the government received criticism from various elements. The process of terminating the work contract had implications for prolonged conflicts in Morotai, because when the dismissal process was carried out (housed) by the Regional Head through the Morotai BKD, he had not issued the Dismissal Decree, but had been exposed through a press conference in the mass media, causing a reaction from the community and the honorary dimorotai process. The process of laying off the honorary received responses from all elements including the Morotai DPRD through a plenary hearing of the faction, which was then submitted to the regional head through the Morotai BKD, regarding the process of reviewing the honorary dismissal, but these recommendations had no effect on the policies implemented. already submitted by the regional head. The implementation of the re-test carried out by the Morotai BKD was only an attempt to dampen frontal mass and honorary actions, so that it had no impact at all on the honorary.